Analysis of Factors That Influence The Disclosure Of Enterprise Risk Management in SMEs - Deni, Asep; Riswanto, Ari (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
Facing the free market era, local governments need to make structural policies that favor and provide incentives for the development and improvement of SMEs performance. The potential of women in community life still has not received a reasonable portion. This needs to be addressed wisely and wisely by the government considering the women from the side of quantity ranks first from the composition of citizens. The type of research used is descriptive research with qualitative method. The discussion in this article is the role of local governments to improve women's empowerment in the economic field by providing women with sewing skills training, micro credit business, and women leadership training. Where the skills training and micro credit business is given to the community where the economic level is still below standard or pre prosperous in order to improve the welfare of the family through the efforts provided by the local government.